Coupled 3D hydrodynamic models for submarine outfalls. Denvironmental hydraulic design and control of multiport diffusers - Bleninger, Tobias (Dissertationsreihe am Institut für Hydromechanik der Universität Karlsruhe, 2007)
The book describes the hydraulic design and environmental impact prediction technologies for such installations. Focus are the hydrodynamics approached by computer models. First, a multiport diffuser design program was developed. Second, two model systems for discharge analysis, CORMIX for the near-field and intermediate-field and Delft3D for the far-field were coupled, and third a regulatory procedure is proposed to license and monitor outfall installations.